Radical prostatectomy assisted by the Da Vinci robotic system in patients with prostate cancer at the Instituto Nacional de Enfermedades Neoplásicas - Destefano-Urrutia, Víctor Alberto (2025)
Introduction. Pancreatic cancer has an unfavorable prognosis. Surgery is the only potentially curative treatment, but complications affect approximately 40% of patients, hindering recovery and long-term outcomes. Objective. identify potential risk factors for perioperative complications in patients undergoing surgery for pancreatic ductal adenocarcinoma (PDAC). Methods. A retrospective study was conducted including 77 patients who underwent surgery for PDAC at a private clinic in Peru between December 2014 and September 2023. Sociodemographic, clinical, and surgical variables were collected. Perioperative complications included postoperative pancreatic fistula (POPF), delayed gastric emptying (DGE), and intraoperative bleeding. Patients were categorized according to the presence of complications, and associations were evaluated using adjusted relative risk (aRR). Results. Of the 77 patients, 35 (45,5%) experienced at least one perioperative complication. Intraoperative bleeding was the most common (20,8%). In the adjusted model, female sex was significantly associated with a lower risk of intraoperative bleeding (adjusted aRR: 0,34; 95% CI: 0,13-0,86; p = 0,022). No significant associations were identified for POPF or DGE. Conclusions. In this cohort, approximately 45% of patients experienced at least one perioperative complication. Female patients showed a significantly lower risk of intraoperative bleeding. No significant predictive factors were identified for POPF or DGE.